Hippocampal and entorhinal cortex volume decline in cognitively intact elderly - Thomann, Philipp; Nolte, Henrike Maria; Menzel, Philipp; Wolf, Robert Christian; Essig, Marco; Schröder, Johannes (Psychiatry research, 2013)
Studying the distribution and chronological sequence of brain morphological changes that occur in normal aging is crucial for understanding the mechanisms underlying these alterations and for distinguishing them from pathological processes. Whether the hippocampal formation is subjected to or spared from age-related shrinkage still remains controversial. We used magnetic resonance imaging (MRI) in order to assess hippocampal and entorhinal morphology in two population-based cognitively unimpaired cohorts (aged 53-55 years and 73-75 years, respectively) matched for gender, education, handedness, and apolipoprotein E status. Voxel-based morphometry (VBM-DARTEL) and shape analysis (FSL-FIRST) revealed significant bihemispheric age-related shrinkage of subiculum and cornu ammonis as well as of the entorhinal cortex (investigated with VBM only). The results lend further support to an effect of aging on medial temporal lobe morphology and thus may be of importance for the interpretation of structural imaging findings, especially in those diseases that are typically related to advancing age, as well as for the interpretation of functional imaging studies, where age-related differences in hippocampal activation may—to a locally varying degree—be explained by morphometric alterations.